Diversity in Clinical Trials — Next Steps - Rosen, Clifford J.; Cook, Nakela L.; Wilkins, Consuelo H. (The New England journal of medicine, 2022)
What are the next steps in ensuring that participants in clinical trials reflect the diversity of the populations affected by the diseases under study? Clifford Rosen moderates a Perspective Roundtable examining this topic.